2014
DOI: 10.1021/co500051z
|View full text |Cite
|
Sign up to set email alerts
|

Solid-Phase Library Synthesis of Bi-Functional Derivatives of Oleanolic and Maslinic Acids and Their Cytotoxicity on Three Cancer Cell Lines

Abstract: A wide set of 264 compounds has been semisynthesized with high yields and purities. These compounds have been obtained through easy synthetic processes based on a solid-phase combinatorial methodology. All the members of this library have one central core of a natural pentacyclic triterpene (oleanolic or maslinic acid) and differ by 6 amino acids, coupled with the carboxyl group at C-28 of the triterpenoid skeleton, and by 10 different acyl groups attached to the hydroxyl groups of the A-ring of these molecule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 52 publications
2
29
0
Order By: Relevance
“…Notable among these products are pentacyclic triterpene compounds (oleanolic and maslinic acids) [37]. These natural pentacyclic triterpene compounds have revealed a wide variety of biological activities such as antiproliferative, anti-inflammatory, antiarthritic, antidiabetic, antiparasitic, antimicrobial, antiviral, anticancer, and hepatoprotective agents [38][39][40][41][42][43][44][45][46][47][48][49][50][51][52].…”
Section: Introductionmentioning
confidence: 99%
“…Notable among these products are pentacyclic triterpene compounds (oleanolic and maslinic acids) [37]. These natural pentacyclic triterpene compounds have revealed a wide variety of biological activities such as antiproliferative, anti-inflammatory, antiarthritic, antidiabetic, antiparasitic, antimicrobial, antiviral, anticancer, and hepatoprotective agents [38][39][40][41][42][43][44][45][46][47][48][49][50][51][52].…”
Section: Introductionmentioning
confidence: 99%
“…or acyl chloride (4 equiv.) to get acyl oleanolic acid compounds (9)(10)(11)(12)(13)(14) at moderate yields of 61-89%. These acyl oleanolic acid 9-14 (1 equiv.)…”
Section: Synthesismentioning
confidence: 99%
“…And introduction of an extra N-substituent led to an increase in cytotoxicity (Kommera et al, 2010). (Parra et al, 2014) have shown that oleanolic and maslinic acids derivatives differing by 6 amino acids, coupled with the carboxyl group at C-28 of the triterpenoid skeleton, and by 10 different acyl groups attached to the hydroxyl groups of the A-ring, are more cytotoxic toward cancer cell lines B16-F10, HT29 and Hep G2 than their corresponding precursors.…”
Section: Introductionmentioning
confidence: 99%